You Tube Videos as a Tool to Improve Indonesian EFL Students' Pronounciation Skills : A Special Case on the Dhar Mann Channel - Harum Natasha (ELITE Association Indonesia, 2023)
ABSTRACT Most EFL students in Indonesia have struggled to improve their English skills. They have limited chances to speak or listen to native English speakers directly. They may have many opportunities to practice their English among their fellows in the English department, but they lack the opportunity to experience conversations with native speakers. This article recommends using videos from Youtube to increase EFL students' pronunciation skills by self-learning, especially by watching the Dhar Mann Youtube channel. The objective of this article is to prove that by watching Dhar Mann channel the EFL students will get some benefits related to pronunciation skills: (i) to be aware of correct stress on English words, (ii) to be aware of correct stress in English sentences, (iii) to be aware of correct intonation in English sentences, (iv) to be aware of correct pronunciation on linking in English sentences. Some recommendations will be added at the end part of the article. Keywords: Benefits from youtube videos; pronunciation videos; pronunciation errors; pronunciation subskills; EFL students